Solve for a a-6+(a-4)=0

Math
a-6+(a-4)=0
Simplify a-6+a-4.
Tap for more steps…
Add a and a.
2a-6-4=0
Subtract 4 from -6.
2a-10=0
2a-10=0
Add 10 to both sides of the equation.
2a=10
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2a=10 by 2.
2a2=102
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2a2=102
Divide a by 1.
a=102
a=102
Divide 10 by 2.
a=5
a=5
Solve for a a-6+(a-4)=0

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top